SIGNIFICANCE OF PERFUSION DEFECTS ON DIPYRIDAMOLE THALLIUM CARDIAC SPECT IN PATIENTS WITH LEFT BUNDLE BRANCH BLOCK - Ali, Muzaffar; Mallick, Nadeem Hayat; Abid, Abdul Rehman; Haq, Samra; Ayub, Muhammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Left Bundle Branch Block (LBBB) is a known cause of false positive results in myocardial perfusion studies. We aimed at investigation of correlation between degree of severity of perfusion defect on cardiac Single Photon Emission Computed Tomography (SPECT) and presence of coronary artery disease on angiography in patients with LBBB. Study Design: This was an analytical study and was carried out at Department of Nuclear Cardiology and Department of Cardiac Catheterisation of Punjab Institute of Cardiology, Lahore from January 2007 to April 2007. Methods: In this study patients having LBBB without known coronary artery disease (CAD) referred for myocardial perfusion studies to the Nuclear Cardiology Department from outpatient, indoor and emergency departments were included. Thallium201 stress/rest SinglePhoton Emission Tomography (SPECT) acquisition scanning was performed. The myocardial perfusion pattern was classified as normal, fixed defect and reversible defect. Coronary angiography was used to confirm CAD only in patients with abnormal scan. Results: Thirty consecutive patients having LBBB were studied. All patients underwent myocardial perfusion imaging using dipyridamole pharmacologic stress. Fourteen patients (47%) revealed normal Thallium201 uptake and distribution at the septum. Reversible defects were noted in 13 (43%) patients. Fixed defects were noted in 3 (10%) patients. Among four patients with mild perfusion defects only 1 (25%) had significant coronary artery disease. In patients with moderate perfusion defects, coronary angiogram was positive for significant coronary artery disease in 1 (33%) patient. In six patients having severe perfusion defects significant coronary artery disease was noted in 5 (83%) patients. All patients with fixed defects had significant coronary artery disease. False positive studies were found to be significantly greater in patients with reversible defects particularly with mild to moderate defects. Conclusions: Patients with left bundle branch block showing moderate to severe reversible perfusion defects on dipyridamole thallium cardiac SPECT have high likelihood of coronary artery disease. Keywords: Left bundle branch block, Coronary artery disease, Thallium201 stress test, Myocardial perfusion imaging, Single-photon emission computed tomography (SPECT).